2007
DOI: 10.2754/avb200776s8s011
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular versus Subcutaneous Administration of Iron Dextran in Suckling Piglets

Abstract: Svoboda M., J. Drábek: Intramuscular versus Subcutaneous Administration of Iron Dextran in Suckling Piglets. Acta Vet. Brno 2007, 76: S11-S15.The aim of the study was to compare the development of red blood cell indices after subcutaneous versus intramuscular administration of iron dextran to suckling piglets during early postnatal period. The piglets in group I (n = 17) were injected subcutaneously (into groin) with 200 mg Fe 3+ as iron dextran on day 3 of life. In group II (n = 16), the piglets received intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…Obviously, injection of high amounts of iron rectifies neonatal IDA in pigs as exemplified in this study and many others [10], [11], [12], [13]. However, it is accompanied by the risk of excessive hepcidin synthesis, which in turn may impair both the utilization of supplemental iron deposited in RES macrophages and the absorption of dietary iron.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…Obviously, injection of high amounts of iron rectifies neonatal IDA in pigs as exemplified in this study and many others [10], [11], [12], [13]. However, it is accompanied by the risk of excessive hepcidin synthesis, which in turn may impair both the utilization of supplemental iron deposited in RES macrophages and the absorption of dietary iron.…”
Section: Resultsmentioning
confidence: 66%
“…Moreover, the molecular machinery responsible for iron absorption in newborn piglets is not fully developed, and this may explain a reduced responsiveness of these animals to oral iron therapy [8], [9]. Consequently, the use of parenteral injection of exogenous iron to prevent deepening iron deficiency in suckling piglets has been well documented and is obligatory in pig breeding [10], [11], [12]. Various iron supplementation strategies (in terms of time and route of iron administration as well as the amount and the form of supplemental iron) have been tested and many of them proved to be beneficial in correcting IDA in newborn piglets as evaluated by measuring their RBC indices and serum iron status [10], [11], [12], [13], [14], [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another option is subcutaneous (s.c.) administration. Svoboda and Drabek (2007) found that it has the same efficacy as i.m. injection.…”
Section: Administration Techniquementioning
confidence: 93%
“…In order to ensure that a selected therapy has a positive effect on growth performance and production parameters several studies were conducted [9,12,18,19,20,21,22,23,24,25,26,27,28]. Svoboda and Drabek (2004) report that 3-day--old piglets injected with iron showed significant increase in haematological parameters (Hb, MCV, MCH, MCHC, PI) on the 21st day of life, whereas piglets from no treatment group developed hypochromic anaemia [29]. In the latter group iron deficiency resulted also in considerably lower body weights on the 21st day of life compared to treated groups.…”
Section: Introductionmentioning
confidence: 99%